ANALISIS PENGGUNAAN UANG ELEKTRONIK DENGAN METODE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 (UTAUT2) - Muhammad Fachril Husain Jeddawi; Lilik Noor Yuliati; Dodik Ridho Nurrochmat (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2020)
Data from the Indonesian Financial Technology Association (IFA) and OJK in 2016 showed that the largestpercentage in financial technology was payment sector. However, the Central Jakarta survey data in 2017shows that the cash payment method is still the consumer’s main choice of 77% in making payments. Thecash payment method is mostly chosen because it is considered more measurable, accepted everywhereand practical. This research took place in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek).The answers to the research are arranged using a Likert scale to be processed with Structural EquationModeling (SEM). The population in this study is millennial generation aged 18-36 years in Jabodetabekwith the criteria of respondents is users of online transactions. The results showed that transportationservices had the largest percentage in online transactions of 37.33%. As many as 67.72% of users getinformation about the use of electronic money applications from the internet. The results of the study alsoshowed that 56.84% of users used electronic money applications for less than ten times in one month. Themost frequently used product is Go-Pay of 63.16% and the reason for using the most electronic money ispractically 47.02%. The top up nominal balance that is most often done is <Rp 250,000 for 45.61% and the most top up method is via SMS / Internet Banking at 64.21%. Most of the variables inthis study had a significant effect on behavioral intention except facilitation conditions, hedonicmotivation and price values. All direct variables on usage behavior have a significant effect.